The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1111/j.1600-051x.1996.tb01828.x
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of gingival indices for use in therapeutic trials

Abstract: A number of gingival indices have been described which include visual and invasive components, either separately or in combination. In selecting indices for use in gingivitis therapeutic trials, some investigators maintain that only invasive indices should be used, since indices that include a bleeding-on-provocation component are deemed to be the most objective. Other investigators, however, maintain that non-invasive indices are the more appropriate insofar as invasive procedures will not only disrupt the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Probing force and position, probe design and depth of insertion of the probe may be some examples of variables that are difficult to control during assessment of gingival inflammation. 18 These are some possible explanations for the complexity involved in reproducing gingival indices, including the repeated recordings of GBI performed in the present study in sequence 3. Thus, high kappa coefficient values (> 0.61) 19 are not expected for replicate recordings of GBI.…”
Section: Discussionmentioning
confidence: 79%
“…Probing force and position, probe design and depth of insertion of the probe may be some examples of variables that are difficult to control during assessment of gingival inflammation. 18 These are some possible explanations for the complexity involved in reproducing gingival indices, including the repeated recordings of GBI performed in the present study in sequence 3. Thus, high kappa coefficient values (> 0.61) 19 are not expected for replicate recordings of GBI.…”
Section: Discussionmentioning
confidence: 79%
“…(30,31) In addition, MGI has demonstrated high sensitivity for assessing resolution and progression of gingivitis. (32) Studies have indicated that MGI and BI correlate well and should produce comparable results when used together in a clinical trial. (32) Therefore, significantly lower BI and MGI scores in the text message group at T2 should be viewed as strong evidence of the effectiveness of the text messaging.…”
Section: Discussionmentioning
confidence: 99%
“…Indices measuring a bleeding component can be used in clinical trials with success [24], but non-invasive and invasive gingival indices include both objective and subjective aspects, and the scientific evidence does not support the statement that invasive indices are truly objective. Therefore, using a visual index to assess gingivitis can be an alternative to an invasive index [25].…”
Section: Discussionmentioning
confidence: 99%